Alpha-Synuclein Pathology Coincides With Increased Number of Early Stage Neural Progenitors in the Adult Hippocampus - Bender, Hannah; Fietz, Simone A.; Richter, Franziska; Stanojlovic, Milos (Frontiers in Cell and Developmental Biology, 2021)
Alpha-synuclein pathology driven impairment in adult neurogenesis was proposed as a potential cause of, or at least contributor to, memory impairment observed in both patients and animal models of Parkinson’s disease (PD) and Dementia with Lewy Bodies (DLB). Mice overexpressing wild-type alpha-synuclein under the Thy-1 promoter (Thy1-aSyn, line 61) uniquely replicate early cognitive deficits together with multiple other characteristic motor and non-motor symptoms, alpha-synuclein pathology and dopamine loss. Here we report overt intracellular accumulation of phosphorylated alpha-synuclein in the hippocampus of these transgenic mice. To test whether this alters adult neurogenesis and total number of mature neurons, we employed immunohistochemistry and an unbiased stereology approach to quantify the distinct neural progenitor cells and neurons in the hippocampal granule cell layer and subgranular zone of 6 (prodromal stage) and 16-month (dopamine loss) old Thy1-aSyn mice. Surprisingly, we observed an increase in the number of early stage, i.e., Pax6 expressing, progenitors whereas the numbers of late stage, i.e., Tbr2 expressing, progenitors and neurons were not altered. Astroglia marker was increased in the hippocampus of transgenic mice, but this was not specific to the regions where adult neurogenesis takes place, arguing against a commitment of additional early stage progenitors to the astroglia lineage. Together, this uncovers a novel aspect of alpha-synuclein pathology in adult neurogenesis. Studying its mechanisms in Thy1-aSyn mice could lead to discovery of effective therapeutic interventions for cognitive dysfunction in PD and DLB.